Kombinasi Survei Terestrial dan Satelit Navigasi untuk Pendefinisian Koordinat Titik Pemantauan Candi Prambanan - Muryamto, Rochmad; Panuntun, Hidayat; Ilmawan, Hanif; Arrofiqoh, Erlyna Noor; Setyawan, Afradon Aditya; Taftazani, Muhammad Iqbal (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Prambanan Temple was built on an unstable soil structure—a layer of sandy soil with medium density. While on the west side, there are faults in the Opak River which could affect the stability of Prambanan Temple. Due to those situations, periodic monitoring of geometric aspects is necessary. This research has succeeded in defining X, Y, Z and φ, λ, h coordinates of Monitoring Points based on GPS observations which was post-processed using GAMIT/GLOBK software. The orthometric height (H) of all Monitoring Points had been obtained from the height difference survey tied to the TTG-852 reference point and calculated using the least square adjustment method. The position of Prambanan Temple was obtained by measuring the reflector mounted on the body of the temple using resection method. The results could be used as reference points in monitoring deformation in the following years.